Storage container for binder for secondary battery and binder product for secondary battery

By using a resin composition made of a high molecular weight polyolefin resin, the problem of easy leakage and insufficient adhesiveness of the binder composition for secondary batteries during long-term storage has been solved, and high adhesiveness and long-term stability have been achieved.

CN119366005APending Publication Date: 2025-01-24ZEON CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202380049877.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-30
Filing Date
2023-09-01
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The prior art is difficult to improve the adhesion of the adhesive composition for secondary batteries while inhibiting the generation of agglomerates, and the adhesive composition may leak from the container during long-term storage, resulting in deterioration of the container.

Method used

Use a adhesive liquid container for the secondary battery to use the resin comprising a resin containing more than 400,000 or more resin as the main ingredient to ensure that the wall thickness of the capacity department is more than 2.5mm, and 72 is displayed in the environmental stress cracking test. Duration of more than hours.

Benefits of technology

It realizes the adhesion of the functional layer while inhibiting the production of condensation, and ensure that the adhesive composition is not easy to leak during long -term storage, which enhances the environmental stress cracking properties of the container.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119366005A_ABST
    Figure CN119366005A_ABST
Patent Text Reader

Abstract

The purpose of the present invention is to provide an adhesive storage container for a secondary battery and an adhesive product for a secondary battery, which can be stored for a long period of time even when an adhesive composition that can improve the adhesiveness of a functional layer while suppressing the generation of agglomerates is provided. This binder storage container for a secondary battery has a storage part for storing a binder composition for a secondary battery, and is characterized in that the storage part is formed by molding a resin composition containing, as a main component, a polyolefin resin having a weight-average molecular weight of 400000 or more, and the wall thickness of the storage part is 2.5 mm or more. The housing part has durability of 72 hours or more in an environmental stress crack test in accordance with JIS K-6761 using an aqueous solution of sodium dialkylsulfosuccinate at a concentration of 1.5 mass%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an adhesive storage container for a secondary battery and an adhesive product for a secondary battery. Background Art

[0002] Secondary batteries such as lithium-ion secondary batteries are small, lightweight, have high energy density, and can be repeatedly charged and discharged, and have been used in a wide range of applications. In addition, secondary batteries generally have battery components such as electrodes (positive and negative electrodes) and separators that separate the positive and negative electrodes.

[0003] As a battery member of a secondary battery, a member having a functional layer including a binder (binder) and optionally particles (hereinafter referred to as “functional particles”) blended to enable the battery member to exert a desired function is used.

[0004] Specifically, as a separator of a secondary battery, a separator having an adhesive layer containing a binder on a separator substrate, a separator having a heat-resistant layer containing a binder and non-conductive particles as functional particles, etc. are used. In addition, as an electrode of a secondary battery, an electrode having an electrode composite material layer containing a binder and electrode active material particles as functional particles on a current collector is used, and an electrode having an electrode composite material layer on a current collector and further having the above-mentioned adhesive layer and heat-resistant layer on an electrode substrate.

[0005] Conventionally, an adhesive for forming a battery member is stored in a container in the form of an adhesive composition obtained by dissolving or dispersing the adhesive in a solvent such as water (for example, refer to Patent Document 1).

[0006] Here, for the functional layer, in order to make it have good adhesion with the substrate supporting the functional layer, it is required to exert excellent adhesion. Therefore, in recent years, in order to make the functional layer fit well with the substrate, the surface tension of the adhesive composition is reduced, and the generation of the coagulant in the adhesive composition after long-term storage is suppressed while improving the adhesion of the functional layer. For example, in patent document 2, it is recorded that the surface tension of the adhesive composition is reduced and controlled within a specified range, and the inside of the container is hydrophobized.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent document 1: International Publication No. 2015 / 029835;

[0010] Patent document 2: International Publication No. 2022 / 071523. Summary of the invention

[0011] Problem that the invention aims to solve

[0012] The present inventors have studied the use of various emulsifiers in order to further improve the surface tension of the adhesive composition.

[0013] However, according to the research of the present inventors, when an adhesive composition containing an emulsifier is filled into a resin container and stored as an adhesive product for a long period of time (for example, one and a half to two years), the emulsifier in the adhesive product penetrates into the container, thereby deteriorating the container (that is, the environmental stress cracking resistance of the container is reduced). As a result, the container is damaged and the adhesive composition as the content may leak from the container.

[0014] Therefore, an object of the present invention is to provide an adhesive storage container for secondary batteries and an adhesive product for secondary batteries that can store an adhesive composition for a long period of time while suppressing the generation of aggregates and improving the adhesiveness of a functional layer.

[0015] Solutions for solving problems

[0016] The present inventors have conducted in-depth research for the purpose of solving the above-mentioned problems. Then, the present inventors found that if a resin composition containing a polyolefin resin having a weight average molecular weight greater than a specified value is used as a main component to prepare a container for storing an adhesive for a secondary battery, and the wall thickness of the container is greater than a specified value, the container can show a specified durability in a specified environmental stress cracking test, thereby improving the environmental stress cracking resistance of the container, thereby completing the present invention.

[0017] That is, the object of the present invention is to advantageously solve the above-mentioned problems. The present invention is [1] a secondary battery adhesive storage container, which has a housing for housing a secondary battery adhesive composition, the housing being formed by molding a resin composition containing a polyolefin resin having a weight average molecular weight of 400,000 or more as a main component, the housing having a wall thickness of 2.5 mm or more, and the housing having a durability of 72 hours or more in an environmental stress cracking test according to JIS K-6761 using a sodium dialkyl sulfosuccinate aqueous solution having a concentration of 1.5 mass %. Such a secondary battery adhesive storage container can be stored for a long time even if the adhesive composition can improve the adhesion of the functional layer while suppressing the generation of agglomerates.

[0018] In the present invention, the environmental stress cracking test according to JIS K-6761 can be performed by the method described in Examples.

[0019] In addition, in the present invention, the weight average molecular weight of the polyolefin resin can be measured by the method described in Examples.

[0020] [2] In the adhesive storage container for secondary batteries of the above-mentioned [1], the above-mentioned resin composition preferably contains the above-mentioned polyolefin resin having a molecular weight distribution (weight average molecular weight / number average molecular weight) of 9 or more and 13 or less. If the resin composition contains a polyolefin resin having a molecular weight distribution within the above-mentioned specified range and a weight average molecular weight of 400,000 or more, the moldability of the container is improved, thereby enabling the adhesive composition capable of suppressing the generation of agglomerates while improving the adhesion of the functional layer to be stored for a longer period of time.

[0021] In the present invention, the molecular weight distribution of the polyolefin resin can be determined by the method described in Examples.

[0022] [3] In the adhesive storage container for secondary batteries of [1] or [2], the weight average molecular weight of the polyolefin resin is preferably less than 500000. If the weight average molecular weight of the polyolefin resin is less than the upper limit, the moldability of the container is improved, and the adhesive composition that can suppress the generation of agglomerates and improve the adhesion of the functional layer can be stored for a longer period of time.

[0023] [4] In the secondary battery adhesive storage container according to any one of [1] to [3], the polyolefin resin is preferably a high-density polyethylene. If a high-density polyethylene is used, the adhesive composition can be stored for a longer period of time while suppressing the generation of aggregates and improving the adhesiveness of the functional layer.

[0024] [5] In the adhesive storage container for secondary batteries described in any one of [1] to [3], the resin composition is preferably an additive-free polyolefin resin. If the resin composition is an additive-free polyolefin resin, it is possible to suppress the leakage of additives from the container into the adhesive composition, and the adhesive composition can be stored for a longer period of time while suppressing the generation of aggregates and improving the adhesion of the functional layer.

[0025] In the present invention, the "additive-free polyolefin resin" refers to a polyolefin resin to which no additives are actively compounded except for the case where additives are inevitably mixed.

[0026] [6] In the secondary battery adhesive storage container described in any one of [1] to [5], the inner wall surface of the container is preferably treated to be hydrophobic. If the inner wall surface of the container is treated to be hydrophobic, the adhesive composition that can suppress the generation of aggregates and improve the adhesion of the functional layer can be stored for a longer period of time.

[0027] In addition, the present invention aims to advantageously solve the above-mentioned problems. [7] The present invention is an adhesive product for a secondary battery, comprising: an adhesive storage container for a secondary battery according to any one of [1] to [6]; and an adhesive composition contained in a container of the adhesive storage container for a secondary battery, wherein the surface tension of the adhesive composition is 20 mN / m or more and 60 mN / m or less. The adhesive product for a secondary battery is unlikely to produce aggregates in the adhesive composition even when stored for a long time, and can form a functional layer with excellent adhesion using the adhesive composition, and can store the adhesive composition for a long time.

[0028] In the present invention, the surface tension of the adhesive composition can be measured by the method described in Examples.

[0029] [8] In the adhesive product for secondary batteries described in [7] above, the adhesive composition preferably contains a dialkyl sulfosuccinate salt. If the adhesive composition contains a dialkyl sulfosuccinate salt, the surface tension of the adhesive composition can be well controlled to an appropriate value, resulting in improved wettability to adherends such as separators, electrodes, current collectors, and active materials, and good suppression of the generation of agglomerates in the adhesive composition after long-term storage, and sufficient improvement of the adhesion of the functional layer. In addition, if the adhesive storage container for secondary batteries of the present invention is used, even if the adhesive composition contains a dialkyl sulfosuccinate salt, the adhesive composition can be stored for a long time.

[0030] Effects of the Invention

[0031] According to the present invention, it is possible to provide an adhesive storage container for a secondary battery and an adhesive product for a secondary battery that can store an adhesive composition for a long period of time while suppressing the generation of aggregates and improving the adhesion of a functional layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 It is a diagram schematically showing the structure of an example of the adhesive storage container for secondary batteries of the present invention. DETAILED DESCRIPTION

[0033] Hereinafter, embodiments of the present invention will be described in detail.

[0034] The adhesive storage container for secondary batteries of the present invention (hereinafter referred to as "container") is used for the storage and transportation of adhesive compositions for secondary batteries (hereinafter referred to as "adhesive compositions"). In addition, the adhesive product of the present invention is formed by containing the adhesive composition in the container of the present invention for the storage and transportation of the adhesive composition. Moreover, the adhesive product of the present invention can be used when taking out the contained adhesive composition and adding functional particles as needed to prepare a slurry composition for a functional layer (for example, a slurry composition for an electrode, a slurry composition for an adhesive layer, and a slurry composition for a heat-resistant layer). Such a slurry composition for a functional layer can be used to form a functional layer (for example, an electrode composite material layer, an adhesive layer, and a heat-resistant layer) of a secondary battery.

[0035] (Secondary battery adhesive storage container)

[0036] The container of the present invention has at least a receiving portion capable of receiving an adhesive composition. The receiving portion is formed by molding a resin composition containing a polyolefin resin having a weight average molecular weight of 400,000 or more as a main component. In addition, the wall thickness of the receiving portion is 2.5 mm or more. Moreover, the receiving portion has a durability of more than 72 hours in an environmental stress cracking test according to JIS K-6761 using an aqueous solution of sodium dialkyl sulfosuccinate at a concentration of 1.5% by mass. Therefore, even if it is an adhesive composition that can improve the adhesion of the functional layer while suppressing the generation of coagulants, the container of the present invention can be stored for a long time (hereinafter referred to as "the adhesive composition has excellent long-term storage"). In addition, the adhesive composition contained in the container of the present invention is not limited to an adhesive composition that can improve the adhesion of the functional layer while suppressing the generation of coagulants, and the container of the present invention can accommodate any adhesive composition.

[0037] The container may consist of only a container, but from the viewpoint of easy filling and removal of the adhesive composition, the container may include a container and a lid capable of sealing an opening of the container to seal the internal space of the container.

[0038] The shape of the container's storage portion is not particularly limited, and may be any shape such as cylindrical, rectangular, or bag-shaped. The shape of the container's lid is not particularly limited, and may be any shape, as long as it can seal the opening of the storage portion.

[0039] use Figure 1 An example illustrating the shape of a container. Figure 1 Schematically shows the structure of an example of the adhesive storage container for secondary batteries of the present invention. Figure 1In the embodiment, the container 1 has a lid 11 and a container 12. The inner space 14 of the container 1 is partitioned by the inner wall surface 13 of the container 12 and the lid 11, and the lid 11 seals the opening of the container 12.

[0040] <Material>

[0041] The container of the present invention needs to be composed of a resin composition containing a polyolefin resin having a weight average molecular weight of 400,000 or more as a main component. The material of the cover to be used is not particularly limited, and examples thereof include glass, resin, and metal. The resin is not particularly limited, and for example, the resin composition for the housing described below can be used.

[0042] <<Resin composition>>

[0043] The resin composition contains a polyolefin resin having a weight average molecular weight of 400,000 or more as a main component, and optionally further contains an additive.

[0044] In the present invention, “containing a polyolefin resin as a main component” means that the resin composition contains 50% by mass or more of a polyolefin resin.

[0045] The content of the polyolefin resin in the resin composition is usually 50% by mass or more, preferably 80% by mass or more, more preferably 90% by mass or more, further preferably 95% by mass or more, and usually 100% by mass or less, relative to 100% by mass of the total amount of the resin composition.

[0046] [Polyolefin resin]

[0047] The polyolefin resin is not particularly limited, and examples thereof include polyethylene resins such as polyethylene and ethylene / α-olefin copolymers, and polypropylene resins such as polypropylene. These resins may be used alone or in combination of two or more.

[0048] Here, polyethylene resins such as polyethylene and ethylene / α-olefin copolymers are classified as having a density of 0.914 g / cm according to JIS K6760. 3 Above 0.925g / cm 3 The following low-density polyethylene (LDPE), density greater than 0.925g / cm 3 And 0.94g / cm 3 Medium density polyethylene (MDPE) below and density greater than 0.94g / cm 3 In addition, among LDPE, the substance composed of ethylene / α-olefin copolymer is also called linear low-density polyethylene (LLDPE).

[0049] The density of high-density polyethylene is preferably 0.945 g / cm 3 If the density of the high-density polyethylene is greater than or equal to the above lower limit, the long-term storage property of the adhesive composition is more excellent. In addition, in the present invention, the density of the polyethylene can be measured by the method described in the examples.

[0050] The α-olefin in the ethylene / α-olefin copolymer is not particularly limited, and examples thereof include α-olefins having 3 to 20 carbon atoms. Specifically, examples of the α-olefin include 1-propylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-dodecene, 4-methyl-1-pentene, 4-methyl-1-hexene, vinylcyclohexane, vinylcyclohexene, styrene, norbornene, butadiene, isoprene, and the like. 1-hexene is particularly preferred. These α-olefins may be used alone or in combination of two or more.

[0051] Here, the content ratio of the α-olefin unit in the ethylene / α-olefin copolymer is preferably 30 mol % or less.

[0052] From the viewpoint of further improving the long-term storage property of the adhesive composition, the polyolefin resin is preferably a polyethylene resin, wherein, from the viewpoints of operability, productivity, cost, etc., polyethylene is preferred, and high-density polyethylene (HDPE) is more preferred. In addition, from the viewpoint of improving the strength of the container, the polyolefin resin is preferably a mixture of high-density polyethylene and ethylene / α-olefin copolymer, and more preferably a mixture of high-density polyethylene and ethylene / 1-hexene copolymer.

[0053] The ratio of the ethylene / α-olefin copolymer in the polyolefin resin is preferably 5% by mass or more, more preferably 10% by mass or more, and preferably 40% by mass or less, more preferably 30% by mass or less, relative to 100% by mass of the polyolefin resin. If the ratio of the ethylene / α-olefin copolymer is within the above range, the strength of the container can be further improved.

[0054] As described above, the polyolefin resin needs to have a weight average molecular weight of 400,000 or more. When the weight average molecular weight is less than 400,000, the long-term storage property of the adhesive composition cannot be ensured. From the viewpoint of further improving the long-term storage property of the adhesive composition, the weight average molecular weight of the polyolefin resin is preferably 440,000 or more, preferably less than 500,000, and more preferably 480,000 or less.

[0055] In addition, from the perspective of further improving the long-term storage properties of the adhesive composition, the resin composition preferably contains the above-mentioned polyolefin resin having a molecular weight distribution (weight average molecular weight / number average molecular weight) of 9 or more and 13 or less, and more preferably, the molecular weight distribution of all the above-mentioned polyolefin resins contained in the resin composition is 9 or more and 13 or less.

[0056] Here, the molecular weight distribution of the polyolefin resin is preferably 10 or more.

[0057] [additive]

[0058] The additive that can be arbitrarily matched in the resin composition is usually a compound with a molecular weight of less than 1000, and examples thereof include hydrotalcite and a crystal nucleating agent. In addition, the resin composition is preferably a polyolefin resin without addition. That is, the resin composition is preferably a polyolefin resin that does not actively match the additive except for the case where it is inevitably mixed in the above-mentioned polyolefin resin. This is because the additive can be suppressed from seeping from the container to the adhesive composition, and as a result, the generation of agglomerates in the adhesive composition can be further suppressed, and the adhesion of the functional layer can be further improved, and the long-term storage of the adhesive composition can be further improved.

[0059] In order to remove the residual chloride ions etc. used during the polymerization of the above resin, hydrotalcite can be added. The amount of hydrotalcite added also depends on the residual chlorine concentration etc., and the amount of hydrotalcite added is preferably 10 ppm or more, more preferably 100 ppm or more, and preferably 1000 ppm or less, more preferably 500 ppm or less relative to the resin.

[0060] In order to improve the formability and strength of the container, a crystal nucleating agent can be used. As the crystal nucleating agent, sorbitol-based crystal nucleating agents, carboxylic acid metal salt-based crystal nucleating agents, organic phosphoric acid metal salt-based crystal nucleating agents and rosin-based crystal nucleating agents can be cited. From the viewpoint of improving the formability and strength of the container, organic phosphoric acid metal salt-based crystal nucleating agents are preferred.

[0061] The amount of the crystal nucleating agent blended is preferably 10 ppm or more, more preferably 100 ppm or more, and is preferably 5000 ppm or less, more preferably 1000 ppm or less, based on the resin.

[0062] Examples of the sorbitol-based crystal nucleating agent include dibenzylidene sorbitol derivatives described in Japanese Patent Application Laid-Open No. 8-3364; (1,3:2,4)-dibenzylidene sorbitol, 1,3-benzylidene-2,4-p-methylbenzylidene sorbitol, 1,3-benzylidene-2,4-p-ethylbenzylidene sorbitol, 1,3-p-methylbenzylidene-2,4-benzylidene sorbitol, 1,3-p-ethylbenzylidene-2,4-benzylidene sorbitol, 1,3 -p-ethylbenzylidene-2,4-p-methylbenzylidene sorbitol, (1,3:2,4)-di(p-methylbenzylidene) sorbitol, (1,3:2,4)-di(p-ethylbenzylidene) sorbitol, (1,3:2,4)-di(p-propylbenzylidene) sorbitol, (1,3:2,4)-di(p-isopropylbenzylidene) sorbitol, (1,3:2,4)-di(p-butylbenzylidene) sorbitol, (1,3:2,4)-di(p-sec-butylbenzylidene) sorbitol, (1,3:2,4)-di(p-tert-butyl sorbitol, (1,3:2,4)-di(2',4'-dimethylbenzylidene) sorbitol, (1,3:2,4)-di(p-methoxybenzylidene) sorbitol, (1,3:2,4)-di(p-ethoxybenzylidene) sorbitol, 1,3-benzylidene-2,4-p-chlorobenzylidene sorbitol, 1,3-p-chlorobenzylidene-2,4-p-methylbenzylidene sorbitol, 1,3-p-chlorobenzylidene-2,4-p-ethylbenzylidene sorbitol, 1, 3-p-methylbenzylidene-2,4-p-chlorobenzylidene sorbitol, 1,3-p-ethylbenzylidene-2,4-p-chlorobenzylidene sorbitol and (1,3:2,4)-di(p-chlorobenzylidene) sorbitol, etc., and particularly preferred are bis(p-methylbenzylidene) sorbitol, (1,3:2,4)-di(methylbenzylidene) sorbitol, (1,3:2,4)-di(ethylbenzylidene) sorbitol, (1,3:2,4)-di(methoxybenzylidene) sorbitol, and (1,3:2,4)-di(ethoxybenzylidene) sorbitol.

[0063] Examples of the carboxylic acid metal salt-based crystal nucleating agent include sodium adipate, potassium adipate, sodium sebacate, aluminum sebacate, potassium sebacate, sodium benzoate, and aluminum benzoate.

[0064] Examples of the organic phosphoric acid metal salt crystal nucleating agent include metal salts of aromatic organic phosphoric acid esters described in Japanese Patent Application Laid-Open No. 8-3364, sodium 2,2'-methylenebis(4,6-di-tert-butylphenyl)phosphate (e.g., ADK STAB NA-11 manufactured by ADICO Co., Ltd.), sodium bis(4-tert-butylphenyl)phosphate (e.g., ADK STAB NA-10 manufactured by ADICO Co., Ltd.), etc. From the viewpoint of further improving the moldability and strength of the container, sodium 2,2'-methylenebis(4,6-di-tert-butylphenyl)phosphate is particularly preferred.

[0065] Examples of the rosin-based crystal nucleating agent include metal salts of rosin, for example, PINECRYSTAL KM-1500, a crystal nucleating agent manufactured by Arakawa Chemical Industries, Ltd., among other commercial products.

[0066] [Method for preparing resin composition]

[0067] The method for preparing the resin composition is not particularly limited. The resin composition can be prepared, for example, by adding the above-mentioned additives to the above-mentioned polyolefin resin as required, and then kneading the mixture using any kneading device such as a kneading extruder and a Banbury mixer.

[0068] <Thickness>

[0069] The container of the present invention requires that the wall thickness of the receiving portion is more than 2.5mm. When the wall thickness of the receiving portion is less than 2.5mm, the long-term storage property of the adhesive composition cannot be ensured. From the viewpoint of further improving the long-term storage property of the adhesive composition, the wall thickness of the receiving portion is preferably more than 2.6mm, more preferably more than 2.9mm, and more preferably more than 3.1mm. In addition, from the viewpoint of suppressing the container from becoming too heavy, the wall thickness of the receiving portion is preferably less than 4.5mm, more preferably less than 3.6mm.

[0070] <Hydrophobic treatment>

[0071] Preferably, the inner wall surface of the receiving portion is subjected to hydrophobic treatment. This is because by carrying out hydrophobic treatment on the inner wall surface of the receiving portion, it is possible to suppress the emulsifier from penetrating into the inner wall of the receiving portion, and as a result, the long-term storage property of the adhesive composition containing the emulsifier can be further improved. As hydrophobic treatment, the treatment using a silane coupling agent, the treatment using a titanium coupling agent, the treatment using an aluminum coupling agent, the treatment using a fatty acid ester wax, and the treatment using a fluororesin can be cited. They can be used alone or in combination of two or more. Moreover, among these, from the viewpoint of further improving the long-term storage property of the adhesive composition, it is preferred to use the treatment using a silane coupling agent and the treatment using a fluororesin. That is, the inner wall surface of the receiving portion is preferably coated by at least one of the layer (film) consisting of a silane coupling agent and the layer (film) consisting of a fluororesin.

[0072] <<Treatment with silane coupling agent>>

[0073] The silane coupling agent is not particularly limited, and examples thereof include sulfur-containing silane coupling agents such as γ-mercaptopropyltrimethoxysilane, γ-mercaptomethyltrimethoxysilane, γ-mercaptomethyltriethoxysilane, γ-mercaptohexamethyldisilazane, bis(3-triethoxysilylpropyl)tetrasulfane, and bis(3-triethoxysilylpropyl)disulfane; γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropylmethyldimethoxysilane (3-glycidoxypropylmethyldimethoxysilane), β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, γ-glycidoxypropylmethyl Silane coupling agents containing epoxy groups, such as diethoxysilane (3-glycidoxypropylmethyldiethoxysilane); silane coupling agents containing amino groups, such as N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, 3-aminopropyltrimethoxysilane (γ-aminopropyltrimethoxysilane), γ-aminopropyltriethoxysilane, N-2-(aminoethyl)-3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-dimethyl-butylene)propylamine, and N-phenyl-3-aminopropyltrimethoxysilane; γ-methacryloxypropyltrimethoxysilane, Silane coupling agents containing (meth)acryloyloxy groups, such as γ-methacryloxypropyl tri(β-methoxyethoxy)silane, γ-methacryloxypropyl methyldimethoxysilane, γ-methacryloxypropyl methyldiethoxysilane, γ-methacryloxypropyl triethoxysilane, and γ-acryloxypropyl trimethoxysilane; silane coupling agents containing vinyl groups, such as vinyl trimethoxysilane, vinyl triethoxysilane, vinyl tri(β-methoxyethoxy)silane, vinyl trichlorosilane, and vinyl triacetoxysilane; silane coupling agents containing chloropropyl groups, such as 3-chloropropyl trimethoxysilane Silane coupling agent; 3-isocyanate propyl triethoxysilane and other silane coupling agents containing isocyanate groups; styryl trimethoxy silane and other silane coupling agents containing styryl groups; 3-ureidopropyl triethoxy silane and other silane coupling agents containing urea groups; diallyl dimethyl silane and other silane coupling agents containing allyl groups; silane coupling agents containing alkoxy groups such as tetraethoxy silane; silane coupling agents containing phenyl groups such as diphenyl dimethoxy silane; silane coupling agents containing fluorine groups such as trifluoropropyl trimethoxy silane; silane coupling agents containing alkyl groups such as isobutyl trimethoxy silane and cyclohexyl methyl dimethoxy silane, etc. These can be used alone or in combination of two or more. Among these, from the viewpoint of further improving the long-term storage of the adhesive composition, epoxy-containing silane coupling agents are preferred, and (3-glycidoxypropyl methyl dimethoxy silane) is more preferred.

[0074] In addition, the treatment with the silane coupling agent is not particularly limited as long as a layer composed of the silane coupling agent can be formed on the inner wall surface of the housing portion, and a known method can be used. For example, the silane coupling agent is dissolved in a solvent such as water or cyclohexane, the resulting solution is applied to the inner wall surface of the housing portion, and then dried to remove the solvent, thereby forming a layer composed of the silane coupling agent on the inner wall surface of the housing portion.

[0075] <<Treatment with fluororesin>>

[0076] As fluororesin, it is not particularly limited, and for example, polytetrafluoroethylene, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer, tetrafluoroethylene-hexafluoropropylene copolymer, tetrafluoroethylene-ethylene copolymer, polyvinylidene fluoride, polychlorotrifluoroethylene, ethylene-chlorofluoroethylene copolymer, tetrafluoroethylene-perfluoro dioxole copolymer, polyvinyl fluoride, tetrafluoroethylene-propylene copolymer, vinylidene fluoride-hexafluoropropylene copolymer, vinylidene fluoride-tetrafluoroethylene-hexafluoropropylene copolymer, acrylic acid modified product of polytetrafluoroethylene, ester modified product of polytetrafluoroethylene, epoxy modified product of polytetrafluoroethylene, and silane modified product of polytetrafluoroethylene, containing perfluoropolyether group compound. These can be used alone or in combination of two or more. Among these, from the viewpoint of further improving the long-term storage property of the adhesive composition, preferably containing perfluoropolyether group compound.

[0077] In addition, the treatment with fluororesin is not particularly limited as long as a layer composed of fluororesin can be formed on the inner wall surface of the container, and a known method can be used. For example, the fluororesin is dissolved in a solvent such as water or cyclohexane, the resulting solution is applied to the inner wall surface of the container, and then dried to remove the solvent, thereby forming a layer composed of fluororesin on the inner wall surface of the container.

[0078] <Method for manufacturing container>

[0079] The container (the container and any lid) of the present invention is not particularly limited, and can be manufactured by molding the above-mentioned resin composition using known molding methods such as extrusion molding, injection molding, and blow molding. From the viewpoint of manufacturing efficiency and cost, it is preferred to use blow molding to manufacture the container. The wall thickness of the container's container can be controlled by changing the molding conditions.

[0080] The temperature at which the resin composition to be molded is melted and kneaded (hereinafter sometimes referred to as heating temperature) is not particularly limited, but is preferably 180° C. or higher and preferably 250° C. or lower from the viewpoint of moldability.

[0081] The temperature of the metal mold used for molding is not particularly limited, but is preferably 25° C. or higher and preferably 100° C. or lower. When the temperature of the metal mold is within the above range, generation of strain in the obtained container can be suppressed, and the strength of the container can be improved.

[0082] In addition, the container is preferably such that the number of particles with a particle size of 0.5 μm is per 1 ft 3 (28.3L) is molded in a clean environment with a particle size of less than 100,000. If the container is manufactured in such an environment, it is possible to suppress the mixing of foreign matter from the container into the adhesive composition, and as a result, the generation of agglomerates caused by foreign matter in the adhesive composition can be further suppressed. From the viewpoint of further suppressing the generation of agglomerates in the adhesive composition, it is more preferable to mold when the number of particles with a particle size of 0.5 μm is 1 / 1 ft 3 (28.3L) is carried out in a clean environment with less than 50,000 particles, and more preferably, the number of particles with a particle size of 0.5 μm is per 1 ft 3 (28.3L) 40,000 or less in a clean environment.

[0083] In addition, "per 1ft 3 The number of particles having a particle size of 0.5 μm present in (28.3 L) can be determined by the method described in International Publication No. 2016 / 079996.

[0084] (Adhesive products for secondary batteries)

[0085] The adhesive product for secondary batteries of the present invention (hereinafter, also referred to as "adhesive product") comprises an adhesive storage container for secondary batteries and an adhesive composition contained in a container of the container. As the adhesive storage container for secondary batteries, the container of the present invention described above can be used. Here, when the container has a lid, the adhesive composition can be taken out from the opening of the container by removing the lid from the container.

[0086] (Adhesive composition)

[0087] In the adhesive product for secondary batteries of the present invention, the adhesive composition contained in the container of the above-mentioned container requires a surface tension of more than 20mN / m and less than 60mN / m. Moreover, the adhesive composition comprises at least an adhesive and water, and optionally comprises other ingredients such as an emulsifier, a wetting agent, a defoamer, and a preservative. In addition, the adhesive composition preferably does not contain an organic solvent. Specifically, the ratio of the organic solvent contained in the adhesive composition (organic solvent content) is preferably less than 1% by mass, more preferably less than 0.5% by mass, and particularly preferably less than 0.1% by mass.

[0088] <Surface tension>

[0089] As described above, the surface tension of the binder composition needs to be more than 20mN / m and less than 60mN / m, preferably more than 25mN / m, preferably less than 50mN / m, and more preferably less than 40mN / m. When the surface tension of the binder composition is less than 20mN / m, the storage stability decreases. The reason is still uncertain, but it is speculated that when the surface tension of the binder composition is less than 20mN / m, the binder is easily attached to the inner wall of the container in the gap portion of the container (the portion after deducting the volume occupied by the binder composition in the container from the internal volume of the container), and when the film formed by the adhered binder drying falls into the binder composition, the film becomes the starting point, resulting in a decrease in the stability of the slurry composition. On the other hand, it is speculated that when the surface tension of the binder composition is greater than 60mN / m, the affinity with the functional particles and substrate of the binder is reduced, so the adhesion of the functional layer is reduced. Furthermore, when the surface tension of the binder composition is greater than 60 mN / m, the viscosity stability of the slurry composition prepared using the binder composition is impaired due to reduced affinity with the functional particles.

[0090] In addition, the surface tension of the adhesive composition can be controlled by, for example, changing the type and / or amount of the adhesive, emulsifier and / or wetting agent.

[0091] <Adhesive>

[0092] As a binder, there is no particular limitation as long as it has a binding ability, and for example, a water-soluble polymer, a water-insoluble granular polymer that can be dispersed in a dispersion medium such as water, and a combination thereof can be used. As a binder, a granular polymer is particularly preferably used. In addition, in the present invention, the polymer is "water-insoluble" means that when 0.5 g of the polymer is dissolved in 100 g of water at a temperature of 25° C., the insoluble component is 90% by mass or more.

[0093] The water-soluble polymer is not particularly limited, and examples thereof include natural polymers, semi-synthetic polymers, and synthetic polymers. More specifically, examples of water-soluble polymers include natural polymers such as thickening polysaccharides, alginic acid and their salts (e.g., sodium alginate), and starch; semi-synthetic polymers such as carboxymethyl cellulose and their salts obtained by chemically treating natural polymers as raw materials; and synthetic polymers such as polyacrylic acid such as polyvinyl pyrrolidone, cross-linked polyacrylic acid, and non-cross-linked polyacrylic acid.

[0094] The structure of the particulate polymer is not particularly limited, and the particulate polymer may have a core-shell structure having a core portion and a shell portion partially covering the outer surface of the core portion, or may not have such a core-shell structure.

[0095] The volume average particle size of the granular polymer is not particularly limited, and is preferably 100 nm or more and 10 μm or less. In addition, the volume average particle size is the volume average particle size D50 in the particle size distribution (volume basis). The volume average particle size D50 represents the particle size (median particle size) at which the cumulative volume reaches 50% from the small diameter side in the particle size distribution (volume basis). The particle size distribution can be measured by a commercially available particle size distribution measuring device.

[0096] The electrolyte swelling degree of the granular polymer is not particularly limited, but is preferably 110% by mass or more and 1300% by mass or less. The electrolyte swelling degree of the granular polymer can be obtained by the following method. In addition, the electrolyte swelling degree of the granular polymer can be controlled by appropriately changing the composition of the polymer.

[0097] <<Determination method of electrolyte swelling degree>>

[0098] The aqueous dispersion containing the particulate polymer was added to a petri dish made of polytetrafluoroethylene. The aqueous dispersion added to the petri dish was dried at 25°C for 48 hours to obtain a dry film. The obtained film was cut into a size required for a test piece and the weight was measured and recorded as W0.

[0099] Then, the obtained test piece was immersed in an electrolyte solution at a temperature of 60°C for 72 hours. As the electrolyte solution, a mixed solvent of ethylene carbonate (EC), diethyl carbonate (DEC) and vinylene carbonate (VC) (volume mixing ratio: EC / DEC / VC=68.5 / 30 / 1.5) containing 1M LiPF 6 As a supporting electrolyte solution.

[0100] Remove the immersed test piece from the electrolyte and wipe off the electrolyte on the surface of the test piece. Measure the mass of the immersed test piece and record it as W1. Then, use the measured W0 and W1 to calculate the electrolyte swelling degree S (mass %) as S = (W1 / W0) × 100.

[0101] The polymer that can be used as the particulate polymer is not particularly limited, and examples thereof include conjugated diene polymers and acrylic polymers.

[0102] <<Conjugated diene polymer>>

[0103] Conjugated diene polymer refers to a polymer containing conjugated diene monomer units. Moreover, as specific examples of conjugated diene polymers, there are no particular limitations, and examples include: copolymers containing aromatic vinyl monomer units and aliphatic conjugated diene monomer units, such as styrene-butadiene copolymers (SBR); butadiene rubber (BR); copolymers containing conjugated diene monomer units and nitrile-containing monomer units, such as acrylonitrile-butadiene copolymers (acrylic rubber, NBR); and hydrogenated polymers obtained by hydrogenating copolymers containing conjugated diene monomer units and nitrile-containing monomer units.

[0104] Here, the composition of the conjugated diene polymer preferred as the binder is described. The conjugated diene polymer may contain an aliphatic conjugated diene monomer unit and may optionally contain a monomer unit (other monomer unit) other than the aliphatic conjugated diene monomer unit.

[0105] [Aliphatic conjugated diene monomer unit]

[0106] As the aliphatic conjugated diene monomer capable of forming the aliphatic conjugated diene monomer unit, for example, 1,3-butadiene, 2-methyl-1,3-butadiene (isoprene), and 2,3-dimethyl-1,3-butadiene can be mentioned. These can be used alone or in combination of two or more. Moreover, among these, 1,3-butadiene is preferred.

[0107] Here, taking all repeating units in the conjugated diene polymer as 100 mass %, the content ratio of the aliphatic conjugated diene monomer unit in the conjugated diene polymer is preferably 25 mass % or more, more preferably 30 mass % or more, and preferably 60 mass % or less, more preferably 50 mass % or less.

[0108] [Other monomer units]

[0109] As other monomer units, monomer units from known monomers that can copolymerize with the above-mentioned aliphatic conjugated diene monomers can be enumerated. As such monomers, aromatic vinyl monomers, nitrile-containing monomers, (methyl) alkyl acrylate monomers, carboxylic acid-containing monomers, amide-containing monomers, etc. can be enumerated. These can be used alone or in combination of two or more. And, among these, aromatic vinyl monomers, (methyl) alkyl acrylate monomers and carboxylic acid-containing monomers are preferred, aromatic vinyl monomers and carboxylic acid-containing monomers are more preferred, and aromatic vinyl monomers are further preferred. That is, the conjugated diene polymer is particularly preferably an aliphatic conjugated diene-aromatic vinyl copolymer comprising an aliphatic conjugated diene monomer unit and an aromatic vinyl monomer unit.

[0110] -Aromatic vinyl monomer unit-

[0111] As aromatic vinyl monomers capable of forming aromatic vinyl monomer units, for example, styrene, α-methylstyrene, vinyltoluene, and divinylbenzene can be cited. These can be used alone or in combination of two or more. Moreover, among these, styrene is preferred. Here, taking all repeating units in the conjugated diene polymer as 100% by mass, the content ratio of the aromatic vinyl monomer units in the conjugated diene polymer is preferably 5% by mass or more, more preferably 10% by mass or more, preferably 80% by mass or less, and more preferably 70% by mass or less.

[0112] -Nitrile-containing monomer unit-

[0113] As nitrile-containing monomers capable of forming nitrile-containing monomer units, ethylenically unsaturated monomers having nitrile groups can be cited. Specifically, as nitrile-containing monomers, there can be cited: acrylonitrile; α-halogenated acrylonitriles such as α-chloroacrylonitrile and α-bromoacrylonitrile; α-alkylacrylonitrile such as methacrylonitrile and α-ethylacrylonitrile. Among these, acrylonitrile is preferred as the nitrile-containing monomer. In addition, the nitrile-containing monomers can be used alone or in combination of two or more in any ratio. Here, taking all repeating units in the conjugated diene polymer as 100% by mass, the content ratio of the nitrile-containing monomer units in the conjugated diene polymer is preferably 40% by mass or less, and more preferably 30% by mass or less.

[0114] -(Meth)acrylic acid alkyl ester monomer unit-

[0115] Examples of the alkyl (meth)acrylate monomers that can form the alkyl (meth)acrylate monomer units include alkyl acrylates such as methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, tert-butyl acrylate, pentyl acrylate, hexyl acrylate, heptyl acrylate, octyl acrylate, and 2-ethylhexyl acrylate; alkyl methacrylates such as methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, tert-butyl methacrylate, pentyl methacrylate, hexyl methacrylate, heptyl methacrylate, octyl methacrylate, and 2-ethylhexyl methacrylate; and hydroxyl-containing alkyl (meth)acrylates such as 2-hydroxyethyl acrylate, 2-hydroxy methacrylate, 2-hydroxypropyl acrylate, 2-hydroxypropyl methacrylate, hydroxybutyl acrylate, hydroxybutyl methacrylate, and 3-chloro-2-hydroxypropyl methacrylate. These may be used alone or in combination of two or more. Moreover, among these, hydroxyl-containing (meth) alkyl acrylates are preferred, and 2-hydroxyethyl acrylate is more preferred. Here, taking all repeating units in the conjugated diene polymer as 100% by mass, the content ratio of the (meth) alkyl acrylate monomer unit in the conjugated diene polymer is preferably 0.3% by mass or more, more preferably 0.5% by mass or more, further preferably 0.6% by mass or more, preferably 20% by mass or less, and more preferably 15% by mass or less.

[0116] In the present invention, "(meth)acrylic acid" means acrylic acid and / or methacrylic acid.

[0117] -Carboxylic acid group-containing monomer unit

[0118] As the carboxylic acid group-containing monomer capable of forming the carboxylic acid group-containing monomer unit, monocarboxylic acids and their derivatives, dicarboxylic acids and their anhydrides and their derivatives, etc. can be cited. As the monocarboxylic acid, acrylic acid, methacrylic acid, crotonic acid, etc. can be cited. As the derivative of the monocarboxylic acid, 2-ethylacrylic acid, isocrotonic acid, α-acetoxyacrylic acid, (3-trans-aryloxyacrylic acid, α-chloro-(3-E-methoxyacrylic acid, (3-diaminoacrylic acid, etc. can be cited. As the dicarboxylic acid, maleic acid, fumaric acid, itaconic acid, etc. can be cited. As the derivative of the dicarboxylic acid, maleic acid monoesters such as methylmaleic acid, dimethylmaleic acid, phenylmaleic acid, chloromaleic acid, dichloromaleic acid, fluoromaleic acid, butyl maleate, nonyl maleate, decyl maleate, dodecyl maleate, octadecyl maleate, and fluoroalkyl maleate can be cited.

[0119] Examples of the anhydride of dicarboxylic acid include maleic anhydride, acrylic anhydride, methyl maleic anhydride, dimethyl maleic anhydride, and citraconic anhydride. These may be used alone or in combination of two or more. Among these, dicarboxylic acids and their derivatives and anhydrides thereof are preferred, and itaconic acid is more preferred.

[0120] Here, taking all repeating units in the conjugated diene polymer as 100 mass %, the content ratio of the carboxylic acid group-containing monomer unit in the conjugated diene polymer is preferably 2 mass % or more, more preferably 3 mass % or more, preferably 8 mass % or more, more preferably 6 mass % or less, and further preferably 4 mass % or less.

[0121] -Amide-containing monomer units-

[0122] Examples of the amide group-containing monomers that can form amide group-containing monomer units include methacrylamide, acrylamide, dimethylacrylamide, diethylacrylamide, diacetoneacrylamide, hydroxyethylacrylamide, hydroxymethylacrylamide, hydroxypropylacrylamide, hydroxybutylacrylamide, etc. These may be used alone or in combination of two or more at any ratio. Among these, acrylamide is preferred.

[0123] The content ratio of the amide group-containing monomer unit in the conjugated diene polymer is particularly preferably 10% by mass or less, based on 100% by mass of all repeating units in the conjugated diene polymer.

[0124] <<Acrylic polymer>>

[0125] The acrylic polymer is a polymer containing an alkyl (meth)acrylate monomer unit. Here, as the alkyl (meth)acrylate monomer that can form the alkyl (meth)acrylate monomer unit, methyl acrylate, ethyl acrylate, n-butyl acrylate, methyl methacrylate, ethyl methacrylate, 2-ethylhexyl acrylate, etc. can be used. In particular, n-butyl acrylate and 2-ethylhexyl acrylate are preferably used.

[0126] The acrylic polymer that can be used as the binder is not particularly limited, and examples thereof include polymers containing the above-mentioned alkyl (meth)acrylate monomer units, acid group-containing monomer units described below, nitrile group-containing monomer units, and crosslinking monomer units.

[0127] [Acid group-containing monomer unit]

[0128] Examples of the acid group-containing monomer capable of forming the acid group-containing monomer unit include a monomer having a carboxylic acid group, a monomer having a sulfonic acid group, a monomer having a phosphoric acid group, and a monomer having a hydroxyl group.

[0129] In addition, examples of monomers having a carboxylic acid group include monocarboxylic acids and dicarboxylic acids. Examples of monocarboxylic acids include acrylic acid, methacrylic acid, and crotonic acid. Examples of dicarboxylic acids include maleic acid, fumaric acid, and itaconic acid. Methacrylic acid is particularly preferred.

[0130] Examples of the monomer having a sulfonic acid group include vinyl sulfonic acid, methylvinyl sulfonic acid, (meth)allyl sulfonic acid, ethyl (meth)acrylate-2-sulfonate, 2-acrylamide-2-methylpropanesulfonic acid, and 3-allyloxy-2-hydroxypropanesulfonic acid.

[0131] In addition, in this specification, "(meth)allyl group" means an allyl group and / or a methallyl group.

[0132] Furthermore, examples of the monomer having a phosphoric acid group include 2-(meth)acryloyloxyethyl phosphate, methyl-2-(meth)acryloyloxyethyl phosphate, and ethyl-(meth)acryloyloxyethyl phosphate.

[0133] In addition, in this specification, "(meth)acryloyl group" means an acryloyl group and / or a methacryloyl group.

[0134] These acid group-containing monomers may be used alone or in combination of two or more at any ratio.

[0135] [Nitrile-containing monomer unit]

[0136] Examples of nitrile-containing monomers that can form nitrile-containing monomer units include α,β-ethylenically unsaturated nitrile monomers. Specifically, the α,β-ethylenically unsaturated nitrile monomers are not particularly limited as long as they are α,β-ethylenically unsaturated compounds having nitrile groups, and examples thereof include acrylonitrile; α-halogenated acrylonitriles such as α-chloroacrylonitrile and α-bromoacrylonitrile; α-alkyl acrylonitriles such as methacrylonitrile and α-ethylacrylonitrile, etc. Acrylonitrile is particularly preferred.

[0137] These nitrile group-containing monomers may be used alone or in combination of two or more at any ratio.

[0138] [Crosslinking monomer unit]

[0139] The crosslinkable monomer unit refers to a monomer unit that can form a crosslinked structure during or after polymerization by heating or irradiation with energy rays.

[0140] Examples of monomers capable of forming crosslinkable monomer units include, for example, multifunctional monomers having two or more polymerizable reactive groups in the monomer. Examples of such multifunctional monomers include, for example, divinyl compounds such as allyl methacrylate and divinylbenzene; di(meth)acrylate compounds such as diethylene glycol dimethacrylate, ethylene glycol dimethacrylate, diethylene glycol diacrylate, and 1,3-butanediol diacrylate; tri(meth)acrylate compounds such as trimethylolpropane trimethacrylate and trimethylolpropane triacrylate; ethylenically unsaturated monomers containing epoxy groups such as allyl glycidyl ether and glycidyl methacrylate. Allyl methacrylate and allyl glycidyl ether are particularly preferred.

[0141] These crosslinkable monomers may be used alone or in combination of two or more at any ratio.

[0142] [Content ratio of each monomer unit]

[0143] When all repeating units in the acrylic polymer are set to 100% by mass, the content ratio of the (meth) alkyl acrylate monomer unit in the acrylic polymer is preferably 50% by mass or more, more preferably 55% by mass or more, more preferably 58% by mass or more, preferably 98% by mass or less, more preferably 97% by mass or less, and more preferably 96% by mass or less. By making the ratio of the (meth) alkyl acrylate monomer unit above the lower limit of the above range, the adhesion of the functional layer made using the adhesive composition can be improved. In addition, by making the ratio of the (meth) alkyl acrylate monomer unit below the upper limit of the above range, the electrochemical characteristics of electrochemical elements such as secondary batteries with functional layers can be further improved.

[0144] When all repeating units in the acrylic polymer are set to 100% by mass, the content ratio of the acid-containing monomer unit in the acrylic polymer is preferably 0.1% by mass or more, more preferably 0.3% by mass or more, more preferably 0.5% by mass or more, preferably 20% by mass or less, more preferably 10% by mass or less, and more preferably 5% by mass or less. By making the ratio of the acid-containing monomer unit above the above lower limit, the dispersibility of the bonding material in the functional layer can be improved, and the electrochemical characteristics of the secondary battery with the functional layer can be fully improved. In addition, by making the ratio of the acid-containing monomer unit below the above upper limit, the residual moisture content of the functional layer can be reduced, and the electrochemical characteristics of the secondary battery can be fully improved.

[0145] When all repeating units in acrylic acid polymer are set to 100 mass %, the content ratio of the monomeric unit containing nitrile groups in acrylic acid polymer is preferably more than 1 mass %, more preferably more than 2 mass %, preferably below 30 mass %, and particularly preferably below 20 mass %. If the content ratio of the monomeric unit containing nitrile groups is above the above lower limit, the cohesive force of acrylic acid polymer can be improved, and the adhesion of functional layer can be improved. On the other hand, if the content ratio of the monomeric unit containing nitrile groups is below the above upper limit, the flexibility of acrylic acid polymer can be improved.

[0146] When the amount of all monomer units of the acrylic acid polymer is set to 100% by mass, the content ratio of the crosslinkable monomer unit in the acrylic acid polymer is preferably 0.1% by mass or more, more preferably 1.0% by mass or more, and preferably 3.0% by mass or less, more preferably 2.5% by mass or less. By making the ratio of the crosslinkable monomer unit above the above lower limit, the electrochemical characteristics of the secondary battery with the functional layer can be further improved. In addition, by making the ratio of the crosslinkable monomer unit below the above upper limit, the adhesion of the functional layer can be improved.

[0147] <<Method for preparing adhesive>>

[0148] The method for preparing the binder is not particularly limited, and a method of polymerizing a monomer composition containing the above-mentioned monomers by a known method can be used.

[0149] Here, the ratio of each monomer in the monomer composition is usually the same as the ratio of each monomer unit in the desired binder. Moreover, the polymerization method of the binder is not particularly limited, and any method such as solution polymerization, suspension polymerization, bulk polymerization, emulsion polymerization, etc. can be used. In addition, as a polymerization reaction, addition polymerization such as ionic polymerization, free radical polymerization, and active free radical polymerization can be used. Moreover, the emulsifier, dispersant, polymerization initiator, polymerization aid, etc. used for polymerization can use those commonly used, and the amount used can also be set to the amount commonly used. In addition, during polymerization, seed particles can also be used for seed polymerization. In addition, a binder manufactured using a suspension polymerization method or an emulsion polymerization method dispersed in an aqueous solvent is preferred from the perspective of excellent operability during transportation and storage.

[0150] <Emulsifier>

[0151] The adhesive composition preferably contains an emulsifier. By making the adhesive composition contain an emulsifier, the surface tension of the adhesive composition can be controlled to an appropriate value, and as a result, the generation of aggregates in the adhesive composition after long-term storage can be well suppressed and the adhesion of the functional layer can be sufficiently improved.

[0152] Examples of the emulsifier include nonionic emulsifiers such as polyoxyethylene alkyl ethers, polyoxyethylene alkylphenol ethers, polyoxyethylene alkyl esters, and polyoxyethylene sorbitan alkyl esters; anionic emulsifiers such as alkylbenzene sulfonates (e.g., potassium dodecylbenzenesulfonate, sodium dodecylbenzenesulfonate), higher alcohol sulfate ester salts, alkyl sulfosuccinates (e.g., dialkyl sulfosuccinates such as sodium dialkyl sulfosuccinate), sodium salt of β-naphthalenesulfonic acid formaldehyde condensate, dodecyl diphenyl oxide disulfonates (e.g., sodium dodecyl diphenyl oxide disulfonate), and lauryl sulfates (e.g., sodium lauryl sulfate); cationic emulsifiers such as alkyltrimethylammonium chloride, dialkylammonium chloride, and benzyl ammonium chloride; copolymeric emulsifiers such as sulfoesters of α,β-unsaturated carboxylic acids, sulfates of α,β-unsaturated carboxylic acids, and sulfoalkyl aryl ethers; and the like.

[0153] The emulsifier may be used alone or in combination of two or more. Moreover, as the emulsifier, from the viewpoint of improving the wettability to adherends such as separators, electrodes, current collectors, and active materials, and further suppressing the generation of agglomerates in the adhesive composition after long-term storage and further improving the adhesion of the functional layer, an anionic emulsifier is preferred, preferably alkylbenzene sulfonate, sodium salt of β-naphthalenesulfonic acid formaldehyde condensate, dodecyl diphenyl ether disulfonate, lauryl sulfate, alkyl sulfosuccinate, more preferably dialkyl sulfosuccinate salt, and more preferably sodium dialkyl sulfosuccinate.

[0154] The amount of the emulsifier contained in the binder composition is preferably 0.4 mass parts or more relative to 100 mass parts of the binder, preferably 5 mass parts or less, and more preferably 2 mass parts or less. If the content of the emulsifier is 0.4 mass parts or more relative to 100 mass parts of the binder, the adhesion of the functional layer can be further improved while improving the viscosity stability of the slurry composition prepared using the binder composition. In addition, the viscosity stability of the binder composition can be improved. On the other hand, if the content of the emulsifier is 5 mass parts or less relative to 100 mass parts of the binder, the adhesion of the functional layer can be fully improved.

[0155] <Method for preparing adhesive composition>

[0156] The adhesive composition can be obtained by mixing the above-mentioned components in the presence of water.

[0157] For example, the adhesive composition can be prepared by adding and mixing other components such as an emulsifier, a wetting agent, a defoamer, and a preservative to the aqueous solution or aqueous dispersion of the adhesive obtained after the polymerization reaction. In addition, other components such as an emulsifier may also be included in the aqueous solution or aqueous dispersion of the adhesive.

[0158] In addition, from the viewpoint of further suppressing the generation of agglomerates, the binder composition is preferably provided for the treatment of separating and removing foreign matter, etc., before being provided for the "manufacture of binder products" described later. Here, as a method for separating and removing foreign matter from the binder composition, it is preferred to use precision filtration and / or filtering using a magnetic filter, and it is further preferred to use a combination of precision filtration and filtering using a magnetic filter. This is because, if precision filtration is implemented, coarse foreign matter can be reliably removed. In addition, in the case where foreign matter such as metal is mixed into the binder composition, the metal itself penetrates the separator in the secondary battery, or the metal causes current concentration on the negative electrode and causes conductive precipitates to precipitate on the negative electrode, thereby possibly causing a short circuit between the electrodes. However, if filtering using a magnetic filter is implemented, magnetic foreign matter such as metals with magnetism such as iron, nickel, and chromium can be reliably removed.

[0159] In the precision filtration of the adhesive composition, a filter having a mesh size of preferably 5 μm or more and 40 μm or less, more preferably 5 μm or more and 20 μm or less, and further preferably 5 μm or more and 15 μm or less can be used. This is because, when a filter having a mesh size of more than 40 μm is used, it may not be possible to effectively remove coarse foreign matter. In addition, this is because, when a filter having a mesh size of less than 5 μm is used, the filtration speed is reduced, and the productivity of the adhesive composition is reduced.

[0160] <Method for manufacturing adhesive product>

[0161] The adhesive product of the present invention is obtained by filling the container of the container with the adhesive composition. The method of filling the container with the adhesive composition is not particularly limited, and a known method can be used.

[0162] The filling of the adhesive composition is preferably carried out at a particle size of 0.5 μm per 1 ft 3 (28.3L) is carried out in a clean environment with less than 100,000 particles. If filling is carried out under such conditions, it is possible to suppress the mixing of foreign matter from the surrounding environment into the adhesive composition during filling, and as a result, the generation of agglomerates caused by foreign matter in the adhesive composition can be further suppressed. From the viewpoint of further suppressing the generation of agglomerates in the adhesive composition, the filling of the adhesive composition is more preferably carried out at a number of particles with a particle size of 0.5 μm per 1 ft 3 (28.3L) is carried out in a clean environment with less than 50,000 particles, and more preferably, the number of particles with a particle size of 0.5 μm is per 1 ft 3 (28.3L) 40,000 or less in a clean environment.

[0163] Here, the void ratio in the adhesive product (the ratio of the volume of the void portion after deducting the volume occupied by the adhesive composition in the container from the internal volume of the container to the internal volume of the container) is preferably 10% by volume or less. If the void ratio is 10% by volume or less, the generation of agglomerates in the adhesive composition after long-term storage can be further suppressed while further improving the adhesion of the functional layer.

[0164] The adhesive product obtained as described above is preferably stored in an environment with a temperature of 5° C. to 40° C. If the adhesive product is stored in such a temperature range, the generation of aggregates in the adhesive composition can be sufficiently suppressed while preventing the deterioration of the adhesive. As a result, the adhesiveness of the obtained functional layer can be further improved.

[0165] (Application of adhesive products)

[0166] In the adhesive product of the present invention, the adhesive composition filled in the receiving portion of the container can be used to manufacture functional layers such as an electrode composite material layer, an adhesive layer, and a heat-resistant layer.

[0167] Hereinafter, a case where a slurry composition for a heat-resistant layer is prepared using the adhesive composition included in the adhesive product of the present invention to produce a separator having a heat-resistant layer on a separator substrate will be described, but the present invention is not limited thereto.

[0168] <Slurry composition for heat-resistant layer>

[0169] The slurry composition for heat-resistant layer contains non-conductive particles, a binder composition, and other components used as needed.

[0170] <<Non-conductive particles>>

[0171] The non-conductive particles are not particularly limited as long as they have heat resistance, and for example, inorganic particles and organic particles described in International Publication No. 2018 / 173839 can be used.

[0172] <<Adhesive composition>>

[0173] As the adhesive composition, the above-mentioned adhesive composition can be used.

[0174] <<Other ingredients>>

[0175] The other components that can be added to the slurry composition for heat-resistant layer are not particularly limited, and examples thereof include known components such as viscosity modifiers, dispersants, and surfactants. The other components may be used alone or in combination of two or more.

[0176] <<Preparation of slurry composition for heat-resistant layer>>

[0177] The preparation method of the slurry composition for the heat-resistant layer is not particularly limited. For example, the above-mentioned binder composition, non-conductive particles, and other components used as needed can be mixed in the presence of a dispersion medium such as water to prepare the slurry composition for the heat-resistant layer. The mixing method is not particularly limited, and a commonly used stirrer or disperser can be used for mixing.

[0178] <Manufacturing of Spacer>

[0179] The heat-resistant layer can be formed on a separator substrate using the slurry composition for a heat-resistant layer to obtain a separator. Specifically, the heat-resistant layer can be formed on a separator substrate using the following method.

[0180] 1) A method of applying the heat-resistant layer slurry composition to the surface of the spacer substrate and then drying it;

[0181] 2) A method of dipping a spacer substrate in a slurry composition for a heat-resistant layer and then drying the slurry composition; and

[0182] 3) A method in which a heat-resistant layer is produced by applying a slurry composition for a heat-resistant layer onto a release substrate and drying the slurry composition, and the obtained heat-resistant layer is transferred to the surface of a separator substrate.

[0183] Among these, the method 1) is particularly preferred because it is easy to control the thickness of the heat-resistant layer. In detail, the method 1) includes: a step of applying the slurry composition for the heat-resistant layer on the spacer substrate (coating step); and a step of drying the slurry composition for the heat-resistant layer applied on the spacer substrate to form a heat-resistant layer on the spacer substrate (drying step).

[0184] <<Coating process>>

[0185] As a method for applying the above-mentioned heat-resistant layer slurry composition to the spacer substrate, it is not particularly limited, and a known method can be used. Specifically, as a coating method, a scraper method, an immersion method, a reverse roller method, a direct roller method, a gravure method, an extrusion method, a brush coating method, etc. can be used. At this time, the slurry composition can be applied only to one side of the spacer substrate, or it can be applied to both sides. The thickness of the slurry film on the spacer substrate before drying after coating can be appropriately set according to the thickness of the heat-resistant layer obtained by drying.

[0186] Here, as the separator substrate to be coated with the slurry composition for heat-resistant layer, known separator substrates such as microporous films or nonwoven fabrics containing polyolefin resins such as polyethylene and polypropylene, aromatic polyamide resins, and cellulose fibers, and porous resin coatings containing inorganic ceramic powders can be used.

[0187] <<Drying process>>

[0188] The method for drying the slurry composition for the heat-resistant layer on the spacer substrate is not particularly limited, and a known method can be used, for example, a drying method using warm air, hot air, or low-humidity air; a vacuum drying method; a drying method using irradiation with infrared rays, electron beams, etc. By drying the slurry composition on the spacer substrate in this way, a heat-resistant layer can be formed on the spacer substrate, and a spacer having a spacer substrate and a heat-resistant layer can be obtained.

[0189] The separator obtained as described above can be preferably used as a separator for secondary batteries such as lithium ion secondary batteries.

[0190] Example

[0191] Hereinafter, the present invention will be specifically described based on the embodiments, but the present invention is not limited to these embodiments. In addition, in the following description, unless otherwise specified, the "%" and "part" of the expression amount are mass references. In addition, in the polymer manufactured by polymerizing a plurality of monomers, the ratio of the monomer unit formed by polymerizing a certain monomer in the above-mentioned polymer is usually consistent with the ratio (feed ratio) shared by the certain monomer in all the monomers used in the polymerization of the polymer, unless otherwise specified.

[0192] Various measurements and evaluations in Examples and Comparative Examples were performed according to the following methods.

[0193] <Surface tension>

[0194] The surface tension of the adhesive composition was measured by a platinum plate method under an environment of 25° C. using an automatic surface tensiometer (“Dy-300” manufactured by Kyowa Interface Science Co., Ltd.).

[0195] <Molecular Weight and Molecular Weight Distribution of Polyethylene Resin Composition>

[0196] 100 ml of 1,2,4-trichlorobenzene was added to 0.1 g of the polyethylene resin composition, and the mixture was dissolved by shaking at 140°C for 1 hour, and heated and filtered with a 0.5 μm filter. The molecular weight (weight average molecular weight and number average molecular weight) of the 0.1% (w / v) sample solution was measured by gel permeation chromatography (GPC) under the following conditions. Then, the molecular weight distribution (weight average molecular weight / number average molecular weight) was calculated using the obtained measured values.

[0197] Determination conditions:

[0198] Eluent: 1,2,4-trichlorobenzene (TCB) (+ butylated hydroxytoluene (BHT) 0.05%)

[0199] Standard material: polystyrene (PS)

[0200] Sample concentration: 0.1w / v%

[0201] Injection volume: 300μL

[0202] Flow rate: 1.0mL / min

[0203] Column temperature: 140°C

[0204] System temperature: 40℃

[0205] Measuring device: HLC-8321GPC / HT (manufactured by Tosoh Corporation) (RI detector used)

[0206] Column: TSKgel GMH HR- H(20)HT×3 pieces (manufactured by Tosoh Co., Ltd. / 7.8mmI.D.×30cm)

[0207] <Density of Polyethylene Resin Composition>

[0208] The density of the polyethylene resin composition was measured by the A method (water displacement method) in accordance with JIS K-7112.

[0209] <Suppression of Aggregate Generation>

[0210] The adhesive composition (ie, adhesive product) filled in each container manufactured in the embodiment and the comparative example is placed in a thermostatic bath capable of adjusting the storage temperature and stored at 25°C for 90 days. Here, when the storage days are 0 days, 30 days, and 60 days, the adhesive composition is shaken up and down and left and right. After 90 days of storage, the coagulation in the adhesive composition is collected on a 200-mesh stainless steel wire mesh. The collected coagulation is washed with water and dried at 100°C for 1 hour under normal pressure using a dryer to evaporate the water. Then, the amount (mass %) of the dried coagulation is calculated with the solid content in the adhesive composition before storage as a reference (100 mass %), and evaluated according to the following benchmarks. The smaller the amount, the more the generation of the coagulation is suppressed.

[0211] A: The amount of aggregates is less than 0.05% by mass

[0212] B: The amount of aggregates is 0.05 mass % or more and less than 0.1 mass %

[0213] C: The amount of aggregates is 0.1% by mass or more

[0214] <Environmental stress cracking test>

[0215] Ten 38×13 mm test pieces were cut from the side of each container manufactured in the examples and comparative examples. According to JIS K-6761 Appendix JC, the test liquid was changed to a 1.5 mass % aqueous solution of sodium dialkyl sulfosuccinate (product name: NEOCOL P, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.), and an environmental stress cracking test was performed. Every 24 hours, the test piece was visually confirmed for cracking, and the time until more than 5 test pieces cracked was evaluated according to the following criteria. The longer the time, the higher the durability (environmental stress cracking resistance) of the container, and the longer the adhesive composition can be stored in the container.

[0216] A: More than 168 hours

[0217] B: 120 hours or more and less than 168 hours

[0218] C: 72 hours or more and less than 120 hours

[0219] D: Less than 72 hours

[0220] <Peel Strength>

[0221] Each spacer manufactured in the embodiment and the comparative example was cut into a width of 10 mm and a length of 50 mm as a test piece. In addition, a SUS plate with a double-sided tape (made by Nitto Denko, No. 5608) was prepared, and the surface of the heat-resistant layer of the above test piece was pasted on the double-sided tape. Then, the peel strength when one end of the spacer substrate was pulled and peeled off at a speed of 50 mm / min in a manner that the peeling surface was 180° was measured, and evaluated according to the following criteria.

[0222] A: Peel strength is 20N / m or more

[0223] B: Peel strength is 15 N / m or more and less than 20 N / m

[0224] C: Peel strength less than 15N / m

[0225] <Production Example 1-1> (Preparation of Granular Polymer 1)

[0226] Into a reactor equipped with a stirrer, 70 parts of ion exchange water, 0.15 parts of sodium lauryl sulfate ("Emal (registered trademark) 2F" manufactured by Kao Chemical Co., Ltd.) as an emulsifier, and 0.5 parts of ammonium persulfate were respectively supplied, the gas phase was replaced with nitrogen, and the temperature was raised to 60°C.

[0227] On the other hand, 50 parts of ion exchange water, 0.5 parts of sodium dodecylbenzene sulfonate as a dispersant, 94.2 parts of n-butyl acrylate (BA) as a (meth) alkyl acrylate monomer, 2 parts of methacrylic acid (MAA) as an acid group-containing monomer, 2 parts of acrylonitrile as a nitrile group-containing monomer, 0.3 parts of allyl methacrylate (AMA) as a crosslinking monomer, and 1.5 parts of allyl glycidyl ether (AGE) were mixed in another container to obtain a monomer composition. The monomer composition was continuously added to the above-mentioned reactor for 4 hours to polymerize. During the addition, the reaction was carried out at 60°C. After the addition was terminated, the reaction was further terminated by stirring at 70°C for 3 hours to produce an aqueous dispersion 1 (binder 1 for secondary batteries) containing a granular polymer.

[0228] <Production Example 1-2> (Preparation of Granular Polymer 2)

[0229] Into a reactor equipped with a stirrer, 70 parts of ion exchange water, 0.15 parts of sodium lauryl sulfate ("Emal (registered trademark) 2F" manufactured by Kao Chemical Co., Ltd.) as an emulsifier, and 0.5 parts of ammonium persulfate were respectively supplied, the gas phase was replaced with nitrogen, and the temperature was raised to 60°C.

[0230] On the other hand, 50 parts of ion exchange water, 0.2 parts of sodium dodecylbenzene sulfonate as a dispersant, and 94.2 parts of n-butyl acrylate (BA) as a (meth) alkyl acrylate monomer, 2 parts of methacrylic acid (MAA) as an acid group-containing monomer, 2 parts of acrylonitrile (AN) as a nitrile group-containing monomer, 0.3 parts of allyl methacrylate (AMA) as a crosslinking monomer, and 1.5 parts of allyl glycidyl ether (AGE) were mixed in another container to obtain a monomer composition. The monomer composition was continuously added to the above-mentioned reactor over 4 hours for polymerization. During the addition, the reaction was carried out at 60°C. After the addition was terminated, the reaction was further terminated by stirring at 70°C for 3 hours to produce an aqueous dispersion 2 (binder 2 for secondary batteries) containing a granular polymer.

[0231] <Production Example 1-3> (Preparation of Granular Polymer 3)

[0232] In a 5MPa pressure-resistant container with a stirrer, 3.8 parts of styrene as an aromatic vinyl monomer, 0.2 parts of methacrylic acid as a carboxylic acid group-containing monomer, 100 parts of ion exchange water, 0.7 parts of dodecylbenzenesulfonic acid as an emulsifier, 0.1 parts of α-methylstyrene dimer as a chain transfer agent, and 0.3 parts of potassium persulfate as a polymerization initiator were added for core formation, and stirred thoroughly. Then, the temperature was raised to 60°C to initiate polymerization, and the polymerization was continued until the polymerization conversion rate reached 98% to obtain seed particles. Next, in the same pressure-resistant container, 16 parts of acrylonitrile as a nitrile group-containing monomer, 30 parts of 1,3-butadiene as an aliphatic conjugated diene monomer, 0.3 parts of sodium dodecylbenzenesulfonate as an emulsifier, 50 parts of ion exchange water, and 0.4 parts of potassium persulfate as a polymerization initiator were added under stirring. The temperature was raised to 60° C. and polymerization was continued until the polymerization conversion rate reached 80%, thereby obtaining an aqueous dispersion containing a particulate polymer constituting the core portion.

[0233] The water dispersion was heated to 70°C, and 6 parts of acrylonitrile as a nitrile-containing monomer, 1 part of acrylamide as an amide-containing monomer, 11 parts of 1,3-butadiene as an aliphatic conjugated diene monomer, 21 parts of styrene as an aromatic vinyl monomer, 8 parts of methyl methacrylate as a (meth) alkyl acrylate monomer, 1.5 parts of acrylic acid and 1.5 parts of itaconic acid as carboxylic acid-containing monomers, and 0.4 parts of tert-dodecyl mercaptan as a chain transfer agent were added continuously to form the shell, and the polymerization was continued. When the polymerization conversion rate reached 96%, the reaction was terminated by cooling, and an aqueous dispersion of a granular polymer having a core-shell structure in which the outer surface of the core was entirely covered by the shell was obtained. A 5% sodium hydroxide aqueous solution was added to the obtained aqueous dispersion containing the granular polymer to adjust the pH to 8. Furthermore, 0.05 parts of a mineral oil-based defoaming agent (manufactured by Seiko PMC Co., Ltd., product name "DF6351") was added as a defoaming agent to 100 parts of the binder, and unreacted monomers were removed by heating and reduced pressure distillation to produce an aqueous dispersion 3 containing a particulate polymer (binder 3 for secondary batteries).

[0234] <Manufacturing Example 2-1> (Preparation of Adhesive Composition 1)

[0235] 0.95 parts of sodium dialkyl sulfosuccinate (product name: NEOCOL P, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.), 0.04 parts of a mineral oil-based defoamer (product name "DF6351" manufactured by Seikyo PMC Co., Ltd.), and 0.05 parts of an isothiazolin-based compound (2-methyl-4-isothiazolin-3-one) as a preservative were added and mixed to prepare an adhesive composition 1. The surface tension of the adhesive composition 1 was 26 mN / m.

[0236] <Production Example 2-2> (Preparation of Adhesive Composition 2)

[0237] 0.05 parts of sodium dialkyl sulfosuccinate (product name: NEOCOL P, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.), 0.04 parts of a mineral oil-based defoamer (product name "DF6351" manufactured by Seikyo PMC Co., Ltd.), and 0.05 parts of an isothiazolin-based compound (2-methyl-4-isothiazolin-3-one) as a preservative were added to 100 parts (equivalent to the solid content of the particulate polymer) of the aqueous dispersion 2 containing the particulate polymer prepared in Production Example 1-2 (binder 2 for secondary batteries) and mixed, and ion exchange water was further added to the obtained mixed solution for dilution to prepare a binder composition 2. The surface tension of the binder composition 2 was 55 mN / m.

[0238] <Production Example 2-3> (Preparation of Adhesive Composition 3)

[0239] 0.04 parts of a mineral oil-based defoamer (product name "DF6351" manufactured by Seiko PMC Co., Ltd.) and 0.05 parts of an isothiazolin-based compound (2-methyl-4-isothiazolin-3-one) as a preservative were added to 100 parts (equivalent to the solid content of the particulate polymer) of the aqueous dispersion 1 (binder 1 for secondary batteries) containing the particulate polymer prepared in Production Example 1-1 and mixed to prepare an adhesive composition 3. The surface tension of the adhesive composition 3 was 52 mN / m.

[0240] <Production Example 2-4> (Preparation of Adhesive Composition 4)

[0241] 0.1 parts of sodium dialkylsulfosuccinate (product name: NEOCOL P, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) and 0.1 parts of an isothiazolin-based compound (1,2-benzisothiazolin-3-one) as a preservative were added to 100 parts (equivalent to the solid content of the particulate polymer) of the aqueous dispersion 3 containing the particulate polymer (binder 3 for secondary batteries) prepared in Production Example 1-3 and mixed, and ion exchange water was further added to the obtained mixed solution for dilution to prepare a binder composition 4. The surface tension of the binder composition 4 was 33 mN / m.

[0242] <Manufacturing Example 2-5> (Preparation of Adhesive Composition 5)

[0243] 0.1 parts of an isothiazolin-based compound (1,2-benzisothiazolin-3-one) as a preservative was added to 100 parts (equivalent to the solid content of the particulate polymer) of the aqueous dispersion 3 (binder 3 for secondary batteries) containing the particulate polymer prepared in Production Example 1-3 and mixed, and ion exchange water was further added to the obtained mixed solution for dilution to prepare an adhesive composition 5. The surface tension of the adhesive composition 5 was 40 mN / m.

[0244] <Manufacturing Example 2-6> (Preparation of Adhesive Composition 6)

[0245] 2.5 parts of sodium dialkyl sulfosuccinate (product name: NEOCOL P, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.), 0.04 parts of a mineral oil-based defoamer (product name "DF6351" manufactured by Seikyo PMC Co., Ltd.), and 0.05 parts of an isothiazolin-based compound (2-methyl-4-isothiazolin-3-one) as a preservative were added and mixed to prepare an adhesive composition 6. The surface tension of the adhesive composition 6 was 17 mN / m.

[0246] <Production Example 2-7> (Preparation of Adhesive Composition 7)

[0247] 0.01 parts of sodium dialkyl sulfosuccinate (product name: NEOCOL P, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.), 0.04 parts of a mineral oil-based defoamer (product name "DF6351" manufactured by Seikyo PMC Co., Ltd.), and 0.05 parts of an isothiazolin-based compound (2-methyl-4-isothiazolin-3-one) as a preservative were added and mixed to 100 parts (equivalent to the solid content of the particulate polymer) of the aqueous dispersion 2 containing the particulate polymer (binder 2 for secondary batteries) prepared in Production Example 1-2, and ion exchange water was further added to the obtained mixed solution for dilution to prepare a binder composition 7. The surface tension of the binder composition 7 was 62 mN / m.

[0248] (Example 1)

[0249] <Manufacturing of Container 1>

[0250] By making the weight average molecular weight 440000 and the density 0.946g / cm 3 , polyethylene with a molecular weight distribution of 9.6 was blow molded at a heating temperature of 200°C and a metal mold temperature of 70°C to produce a container 1 with a wall thickness of 3.1 mm and a capacity of 20 L. Then, an environmental stress cracking test was performed on the container 1. The results are shown in Table 1.

[0251] <Manufacturing of Adhesive Product 1>

[0252] 18 kg of the adhesive composition 1 prepared in Production Example 2-1 was microfiltered using a 10 μm filter (product name: NXT10-10U, manufactured by Nihon Pall Ltd.), and then the number of particles with a particle size of 0.5 μm was 40,000 / ft. 3 The adhesive composition filling place of was filled into the container 1 to obtain the adhesive product 1. Then, the suppression of the generation of agglomerates was evaluated using the adhesive product 1. The results are shown in Table 1.

[0253] <Preparation of Slurry Composition for Heat-Resistant Layer>

[0254] Alumina particles (product name: LS-256, manufactured by Nippon Light Metal Co., Ltd., volume average particle size D50 = 0.5 μm) as non-conductive particles, sodium polyacrylate (product name: Aron T-50, manufactured by Toagosei Co., Ltd.) as a dispersant, and carboxymethyl cellulose with an etherification degree of 0.8 to 1.0 (product name: 1220, manufactured by Daicel Fine Chemicals Co., Ltd.) as a viscosity regulator were prepared separately.

[0255] 100 parts of the non-conductive particles and 0.5 parts of the dispersant were mixed with ion exchange water and treated with a bead mill (LMZ015 manufactured by Ashizawa Meimei Technology Co., Ltd.) for 1 hour to obtain a dispersion. Furthermore, 2 parts (solid content equivalent) of an aqueous solution of a viscosity modifier, 3 parts (solid content) of an adhesive composition 1 stored at 25° C. for 90 days as an adhesive product 1, and 0.2 parts of a polyethylene glycol-type surfactant (product name: Noptex E-D 052, manufactured by San Nopco) were mixed with the dispersion to prepare a slurry composition for a heat-resistant layer.

[0256] <Manufacturing of Spacer 1>

[0257] The heat-resistant layer slurry composition was applied to one side of a porous polyethylene substrate (product name: Hipore ND412, manufactured by Asahi Kasei Corporation, thickness: 12 μm) using a table-top coater so that the thickness after drying was 2 μm, and dried at 50° C. for 3 minutes. Thus, a spacer 1 having a heat-resistant layer formed on the spacer substrate was obtained. Then, the peel strength of the spacer 1 was evaluated. The results are shown in Table 1.

[0258] (Example 2)

[0259] <Manufacturing of Container 2>

[0260] Container 2 was produced in the same manner as in Example 1 except that the temperature of the metal mold used in blow molding was changed to 30° C. and the wall thickness of the container was changed to 2.9 mm. Then, an environmental stress cracking test was performed on Container 2. The results are shown in Table 1.

[0261] <Manufacturing of Adhesive Product 2>

[0262] In Example 1, except that the container 2 was used instead of the container 1, the same procedure as in Example 1 was carried out to produce an adhesive product 2, and the suppression of the generation of aggregates was evaluated. The results are shown in Table 1.

[0263] <Manufacturing of Spacer 2>

[0264] In Example 1, except that the binder product 2 was used instead of the binder product 1 to prepare the slurry composition for the heat-resistant layer, the separator 2 was produced in the same manner as in Example 1, and the peel strength was evaluated.

[0265] (Example 3)

[0266] <Manufacturing of Container 3>

[0267] The weight average molecular weight is 500000, the molecular weight distribution is 10.0, and the density is 0.943g / cm 3Container 3 was manufactured in the same manner as in Example 1 except that polyethylene of 100% was used instead of the polyethylene used in Example 1. Then, an environmental stress cracking test was performed on container 3. The results are shown in Table 1.

[0268] <Manufacturing of Adhesive Product 3>

[0269] In Example 1, except that the container 3 was used instead of the container 1, the same procedure as in Example 1 was carried out to produce an adhesive product 3, and the suppression of the generation of aggregates was evaluated. The results are shown in Table 1.

[0270] <Manufacturing of Spacer 3>

[0271] In Example 1, except that the slurry composition for heat-resistant layer was prepared using the binder product 3 instead of the binder product 1, the separator 3 was produced in the same manner as in Example 1, and the peel strength was evaluated.

[0272] (Example 4)

[0273] <Manufacturing of Container 4>

[0274] The weight average molecular weight is 480000, the molecular weight distribution is 12.6, and the density is 0.951g / cm 3 Container 4 was manufactured in the same manner as in Example 1 except that polyethylene of 100% was used instead of the polyethylene used in Example 1 and the wall thickness of the container was changed to 2.9 mm. Then, an environmental stress cracking test was performed on container 4. The results are shown in Table 1.

[0275] <Manufacturing of Adhesive Product 4>

[0276] In Example 1, except that the container 4 was used instead of the container 1, the same procedure as in Example 1 was carried out to produce an adhesive product 4, and the suppression of the generation of aggregates was evaluated. The results are shown in Table 1.

[0277] <Manufacturing of Spacer 4>

[0278] In Example 1, except that the binder product 4 was used instead of the binder product 1 to prepare the slurry composition for the heat-resistant layer, the separator 4 was produced in the same manner as in Example 1, and the peel strength was evaluated.

[0279] (Example 5)

[0280] <Manufacturing of Container 5>

[0281] The weight average molecular weight is 400000, the molecular weight distribution is 12.1, and the density is 0.953g / cm 3Container 5 was manufactured in the same manner as in Example 1 except that polyethylene of 100% was used instead of the polyethylene used in Example 1 and the wall thickness of the container was changed to 2.6 mm. Then, an environmental stress cracking test was performed on container 5. The results are shown in Table 1.

[0282] <Manufacturing of Adhesive Product 5>

[0283] In Example 1, except that the container 5 was used instead of the container 1, the same procedure as in Example 1 was carried out to produce an adhesive product 5, and the suppression of the generation of aggregates was evaluated. The results are shown in Table 1.

[0284] <Manufacturing of Spacer 5>

[0285] In Example 1, except that the slurry composition for heat-resistant layer was prepared using the binder product 5 instead of the binder product 1, the separator 5 was produced in the same manner as in Example 1, and the peel strength was evaluated.

[0286] (Example 6)

[0287] <Manufacturing of Container 6>

[0288] The weight average molecular weight is 440000, the molecular weight distribution is 13.2, and the density is 0.922g / cm 3 Container 6 was manufactured in the same manner as in Example 1 except that low-density polyethylene of 1000 mm was used instead of the polyethylene used in Example 1 and the wall thickness of the container was changed to 3.4 mm. Then, an environmental stress cracking test was performed on container 6. The results are shown in Table 1.

[0289] <Manufacturing of Adhesive Product 6>

[0290] In Example 1, except that the container 6 was used instead of the container 1, the same procedure as in Example 1 was carried out to produce an adhesive product 6, and the suppression of the generation of aggregates was evaluated. The results are shown in Table 1.

[0291] <Manufacturing of Spacer 6>

[0292] In Example 1, except that the slurry composition for heat-resistant layer was prepared using the binder product 6 instead of the binder product 1, the separator 6 was produced in the same manner as in Example 1, and the peel strength was evaluated.

[0293] (Example 7)

[0294] <Manufacturing of Container 7>

[0295] Container 7 was produced in the same manner as in Example 5 except that a polyethylene resin composition prepared as described below was molded instead of the polyethylene used in Example 5. Then, an environmental stress cracking test was performed on Container 7. The results are shown in Table 1.

[0296] <<Preparation of Polyethylene Resin Composition>

[0297] To the polyethylene used in Example 5, 200 ppm of hydrotalcite (product name: DHT-4A, manufactured by Kyowa Chemical Industry Co., Ltd.) was added as an additive based on the polyethylene, and the mixture was fully kneaded at a heating temperature of 200° C. to obtain a polyethylene resin composition.

[0298] <Manufacturing of Adhesive Product 7>

[0299] In Example 1, except that the container 7 was used instead of the container 1, the same procedure as in Example 1 was carried out to produce an adhesive product 7, and the suppression of the generation of aggregates was evaluated. The results are shown in Table 1.

[0300] <Manufacturing of Spacer 7>

[0301] In Example 1, except that the slurry composition for heat-resistant layer was prepared using Adhesive Product 7 instead of Adhesive Product 1, the same procedure as in Example 1 was carried out to produce Separator 7 and evaluate the peel strength.

[0302] (Example 8)

[0303] <Manufacturing of Container 8>

[0304] Container 8 was produced in the same manner as in Example 1 except that a polyethylene resin composition prepared as described below was used instead of the polyethylene used in Example 1, the mold temperature was changed to 30°C, and the wall thickness of the container was changed to 2.9 mm. Then, an environmental stress cracking test was performed on Container 8. The results are shown in Table 1.

[0305] <<Preparation of Polyethylene Resin Composition>

[0306] To the polyethylene used in Example 1, an organic phosphoric acid-based crystal nucleating agent (product name: NA-11, manufactured by Aidi Co., Ltd.) was added as an additive at 500 ppm relative to the polyethylene, and the mixture was fully kneaded at a heating temperature of 200° C. to obtain a polyethylene resin composition.

[0307] <Manufacturing of Adhesive Product 8>

[0308] In Example 1, except that the container 8 was used instead of the container 1, the same procedure as in Example 1 was carried out to produce an adhesive product 8, and the suppression of the generation of aggregates was evaluated. The results are shown in Table 1.

[0309] <Manufacturing of Spacer 8>

[0310] In Example 1, except that the slurry composition for heat-resistant layer was prepared using the binder product 8 instead of the binder product 1, the same procedure as in Example 1 was carried out to produce the separator 8 and evaluate the peel strength.

[0311] (Example 9)

[0312] <Manufacturing of Container 9>

[0313] Container 9 was produced in the same manner as in Example 5 except that a polyethylene resin composition prepared as described below was molded instead of the polyethylene used in Example 5. Then, an environmental stress cracking test was performed on container 9. The results are shown in Table 1.

[0314] <<Preparation of Polyethylene Resin Composition>

[0315] To 90 parts by mass of polyethylene used in Example 5, 10 parts by mass of polyethylene having a weight average molecular weight of 420,000 and a density of 0.933 g / cm 3 , a polyethylene / 1-hexene copolymer (ethylene / 1-hexene=100 / 5 (mass ratio)) having a molecular weight distribution of 12.4 was fully kneaded at a heating temperature of 200° C. to make it uniform, thereby obtaining a polyethylene resin composition.

[0316] <Manufacturing of Adhesive Product 9>

[0317] In Example 1, except that the container 9 was used instead of the container 1, the same procedure as in Example 1 was carried out to produce an adhesive product 9, and the suppression of the generation of aggregates was evaluated. The results are shown in Table 1.

[0318] <Manufacturing of Spacer 9>

[0319] In Example 1, except that the slurry composition for heat-resistant layer was prepared using Adhesive Product 9 instead of Adhesive Product 1, the same procedure as in Example 1 was carried out to produce Separator 9 and evaluate the peel strength.

[0320] (Example 10)

[0321] <Manufacturing of Adhesive Product 10>

[0322] In Example 1, an adhesive product 10 was produced in the same manner as in Example 1, except that the adhesive composition 2 prepared in Production Example 2-2 was filled into the container 1 instead of the adhesive composition 1, and the suppression of the generation of aggregates was evaluated. The results are shown in Table 1.

[0323] <Manufacturing of Spacer 10>

[0324] In Example 1, a separator 10 was produced and the peel strength was evaluated in the same manner as in Example 1 except that the binder product 10 was used instead of the binder product 1 to prepare the slurry composition for the heat-resistant layer.

[0325] (Example 11)

[0326] <Manufacturing of Adhesive Product 11>

[0327] In Example 1, the adhesive product 11 was produced in the same manner as in Example 1, except that the adhesive composition 3 prepared in Production Example 2-3 was filled into the container 1 instead of the adhesive composition 1, and the suppression of the generation of aggregates was evaluated. The results are shown in Table 1.

[0328] <Manufacturing of Spacer 11>

[0329] In Example 1, except that the binder product 11 was used instead of the binder product 1 to prepare the slurry composition for the heat-resistant layer, the separator 11 was produced in the same manner as in Example 1, and the peel strength was evaluated.

[0330] (Example 12)

[0331] <Manufacturing of Adhesive Product 12>

[0332] In Example 1, except that the adhesive composition 4 prepared in Production Example 2-4 was filled into the container 1 instead of the adhesive composition 1, the same procedures as in Example 1 were carried out to produce an adhesive product 12 and evaluate the suppression of the generation of aggregates. The results are shown in Table 1.

[0333] <Manufacturing of Spacer 12>

[0334] In Example 1, except that the binder product 12 was used instead of the binder product 1 to prepare the slurry composition for the heat-resistant layer, the separator 12 was produced in the same manner as in Example 1, and the peel strength was evaluated.

[0335] (Example 13)

[0336] <Manufacturing of Adhesive Product 13>

[0337] In Example 1, except that the adhesive composition 5 prepared in Production Example 2-5 was filled into the container 1 instead of the adhesive composition 1, the same procedures as in Example 1 were carried out to produce an adhesive product 13 and evaluate the suppression of the generation of aggregates. The results are shown in Table 1.

[0338] <Manufacturing of Spacer 13>

[0339] In Example 1, the separator 13 was produced and the peel strength was evaluated in the same manner as in Example 1 except that the adhesive product 13 was used instead of the adhesive product 1 to prepare the slurry for the heat-resistant layer.

[0340] (Comparative Example 1)

[0341] <Manufacturing of Container 10>

[0342] The weight average molecular weight is 300000, the molecular weight distribution is 13.5, and the density is 0.946g / cm 3 The container 10 was manufactured in the same manner as in Example 1 except that the polyethylene used in Example 1 was replaced with polyethylene of 2.8 mm and the wall thickness of the container was changed to 2.8 mm. Then, the environmental stress cracking test was performed on the container 10. The results are shown in Table 1.

[0343] <Manufacturing of Adhesive Product 14>

[0344] In Example 1, except that the container 10 was used instead of the container 1, the same procedure as in Example 1 was carried out to produce an adhesive product 14, and the suppression of the generation of aggregates was evaluated. The results are shown in Table 1.

[0345] <Manufacturing of Spacer 14>

[0346] In Example 1, except that the binder product 14 was used instead of the binder product 1 to prepare the slurry composition for the heat-resistant layer, the separator 14 was produced in the same manner as in Example 1, and the peel strength was evaluated.

[0347] (Comparative Example 2)

[0348] <Manufacturing of Container 11>

[0349] Container 11 was produced in the same manner as in Example 1 except that the wall thickness of the container was changed to 1.4 mm. Then, an environmental stress cracking test was performed on container 11. The results are shown in Table 1.

[0350] <Manufacturing of Adhesive Product 15>

[0351] In Example 1, except that the container 11 was used instead of the container 1, the same procedure as in Example 1 was carried out to produce an adhesive product 15, and the suppression of the generation of aggregates was evaluated. The results are shown in Table 1.

[0352] <Manufacturing of Spacer 15>

[0353] In Example 1, except that the slurry composition for heat-resistant layer was prepared using the binder product 15 instead of the binder product 1, the separator 15 was produced in the same manner as in Example 1, and the peel strength was evaluated.

[0354] (Comparative Example 3)

[0355] <Manufacturing of Container 12>

[0356] The weight average molecular weight is 360000, the molecular weight distribution is 11.6, and the density is 0.960g / cm 3 Container 12 was manufactured in the same manner as in Example 1 except that polyethylene of 100% was used instead of the polyethylene used in Example 1 and the wall thickness of the container was changed to 2.3 mm. Then, an environmental stress cracking test was performed on container 12. The results are shown in Table 1.

[0357] <Manufacturing of Adhesive Product 16>

[0358] In Example 1, except that the container 12 was used instead of the container 1, the same procedure as in Example 1 was carried out to produce an adhesive product 16, and the suppression of the generation of aggregates was evaluated. The results are shown in Table 1.

[0359] <Manufacturing of Spacer 16>

[0360] In Example 1, except that the binder product 16 was used instead of the binder product 1 to prepare the slurry composition for the heat-resistant layer, the same procedure as in Example 1 was carried out to produce the separator 16 and evaluate the peel strength.

[0361] (Reference Example 1)

[0362] <Manufacturing of Adhesive Product 17>

[0363] In Example 1, except that the adhesive composition 6 prepared in Production Example 2-6 was filled into the container 1 instead of the adhesive composition 1, the same procedures as in Example 1 were carried out to produce an adhesive product 17 and evaluate the suppression of the generation of aggregates. The results are shown in Table 1.

[0364] <Manufacturing of Spacer 17>

[0365] In Example 1, except that the slurry composition for heat-resistant layer was prepared using the binder product 17 instead of the binder product 1, the same procedure as in Example 1 was carried out to produce the separator 17 and evaluate the peel strength.

[0366] (Reference Example 2)

[0367] <Manufacturing of Adhesive Product 18>

[0368] In Example 1, except that the adhesive composition 7 prepared in Production Example 2-7 was filled into the container 1 instead of the adhesive composition 1, the same procedures as in Example 1 were carried out to produce an adhesive product 18 and evaluate the suppression of the generation of aggregates. The results are shown in Table 1.

[0369] <Manufacturing of Spacer 18>

[0370] In Example 1, except that the slurry composition for heat-resistant layer was prepared using the binder product 18 instead of the binder product 1, the same procedure as in Example 1 was carried out to produce the separator 18 and evaluate the peel strength.

[0371] [Table 1]

[0372] .

[0373] It can be seen from the examples, comparative examples and reference examples that the adhesive composition with a surface tension of 20 mN / m or more and 60 mN / m or less can suppress the generation of coagulation and improve the adhesion of the functional layer. In addition, it can be seen from the examples and comparative examples that if a resin composition containing a polyolefin resin with a weight average molecular weight of 400,000 or more as a main component is used for molding, and the wall thickness of the container is 2.5 mm or more, even an adhesive composition that can suppress the generation of coagulation and improve the adhesion of the functional layer can be stored for a long time.

[0374] Industrial Applicability

[0375] According to the present invention, it is possible to provide an adhesive storage container for a secondary battery and an adhesive product for a secondary battery that can store an adhesive composition for a long period of time while suppressing the generation of aggregates and improving the adhesion of a functional layer.

[0376] Description of Reference Numerals

[0377] 1: Container

[0378] 11: Cover

[0379] 12: Accommodation

[0380] 13: Inner wall surface

[0381] 14: Internal Space

Claims

1. A secondary battery adhesive storage container having a housing for housing a secondary battery adhesive composition, The housing portion is formed by molding a resin composition containing a polyolefin resin having a weight average molecular weight of 400,000 or more as a main component. The wall thickness of the receiving portion is greater than 2.5 mm. The housing portion has a durability of 72 hours or more in an environmental stress cracking test in accordance with JIS K-6761 using an aqueous solution of sodium dialkyl sulfosuccinate having a concentration of 1.5 mass %.

2. The adhesive storage container for secondary batteries according to claim 1, wherein: The resin composition includes the polyolefin resin having a molecular weight distribution (weight average molecular weight / number average molecular weight) of 9 or more and 13 or less.

3. The adhesive storage container for secondary batteries according to claim 1, wherein: The weight average molecular weight of the polyolefin resin is less than 500,000.

4. The adhesive storage container for secondary batteries according to claim 1, wherein: The polyolefin resin is high-density polyethylene.

5. The adhesive storage container for secondary batteries according to claim 1, wherein The resin composition is an additive-free polyolefin resin.

6. The adhesive storage container for secondary batteries according to claim 1, wherein: The inner wall surface of the accommodation portion is subjected to a hydrophobic treatment.

7. An adhesive product for secondary batteries, comprising: The adhesive storage container for secondary batteries according to any one of claims 1 to 6; and an adhesive composition contained in the containing portion of the adhesive storage container for a secondary battery, The surface tension of the adhesive composition is greater than or equal to 20 mN / m and less than or equal to 60 mN / m.

8. The adhesive product for secondary batteries according to claim 7, wherein: The binder composition comprises a dialkyl sulfosuccinate salt.

Citation Information

Patent Citations

  • Crystalline synthetic resin composition

    JP1996003364A

  • Method for preserving aqueous binder composition for lithium secondary cell

    WO2015029835A1

  • Method for producing binder composition for electrochemical element

    WO2016079996A1

  • Storage method for binder composition

    WO2018173839A1

  • Binder product for secondary batteries

    WO2022071523A1